Addressing Climate Change in Fragile States : An Example from Yemen - Sieghart, Lia Carol (World Bank, Washington, DC, 2015)
It is predicted that the effects of climate change, especially extreme floods and droughts, will significantly affect the worlds fragile and least developed countries. Yemen, with its struggling economy and various levels of fagility and conflict, faces daunting development challenges. Challenged with diminishing water resources, increasing reliance on agriculture half of which is rain-fed and frequent floods and droughts, Yemenis face the daunting task of coping with the potentially devastating effects of climate variability and further climate change as the growth of global greenhouse gas emissions continues apace. It is estimated that climate change induced price increases will increase agricultural gross domestic product (GDP), while decreasing real household incomes and food security. Yemen has approached this task by creating a strategic program for climate resilience, encouraging donor support for climate related projects, and requiring cross-government implementation of climate-smart policies. The pilot program for climate resilience (PPCR) is making the first significant investment in Yemen. The program is demonstrating ways in which climate risk and resilience can be incorporated into developmental planning and the daily decisions of people.